Neutral and anionic square planar palladium(0) complexes stabilized by a silicon Z-type ligand - Ansmann, Nils; Münch, Joshua; Schorpp, Marcel; Greb, Lutz (Angewandte Chemie. International edition, 2023)
Anionic [Pd(0)−X]− ate complex were proposed as key intermediates in Pd-catalyzed cross-coupling for decades, but their isolation remained elusive. Herein, a chelating Lewis acidic bis(amidophenolato)silane is introduced as a strong Z-type ligand which enables the characterization of the first anionic [Pd(0)−X]− ate complex. Intriguingly, these compounds and the neutral L−Pd(0) analogs exhibit a square planar coordination that is highly unusual for a d10 metal. Theoretical methods scrutinize the interaction between the Lewis acidic Si(IV) center and the late transition metal, while reactivity studies shed light on the potential role of anionic additives in oxidative addition reactions.